2015
DOI: 10.1371/journal.pone.0119878
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Levels of the Complement Activation Product C4d in Bronchial Fluids for the Diagnosis of Lung Cancer

Abstract: Molecular markers in bronchial fluids may contribute to the diagnosis of lung cancer. We previously observed a significant increase of C4d-containing complement degradation fragments in bronchoalveolar lavage (BAL) supernatants from lung cancer patients in a cohort of 50 cases and 22 controls (CUN cohort). The present study was designed to determine the diagnostic performance of these complement fragments (hereinafter jointly referred as C4d) in bronchial fluids. C4d levels were determined in BAL supernatants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 35 publications
1
23
0
Order By: Relevance
“…Generally, the complement cascade system is activated to defend a host against microbes during an inflammatory response. The activation of complement and its role in tumor progression is evident in studies conducted for different cancer types, including lung adenocarcinoma [44], breast [45] and thyroid cancer [46]. Consequently, we observed similar processes from ClueGO results where genes involved in inflammation, complement activation and defense response were activated in PD alongside genes responsible for positive regulation of leukocyte chemotaxis.…”
Section: Alkylating Agents -Progressive Disease A) Lung Adenocarcinomasupporting
confidence: 71%
“…Generally, the complement cascade system is activated to defend a host against microbes during an inflammatory response. The activation of complement and its role in tumor progression is evident in studies conducted for different cancer types, including lung adenocarcinoma [44], breast [45] and thyroid cancer [46]. Consequently, we observed similar processes from ClueGO results where genes involved in inflammation, complement activation and defense response were activated in PD alongside genes responsible for positive regulation of leukocyte chemotaxis.…”
Section: Alkylating Agents -Progressive Disease A) Lung Adenocarcinomasupporting
confidence: 71%
“…It was also reported that the silencing sortilin expression in tumor cells may introduce sortilin as a potential candidate for developing a novel targeted therapy in patients with ovarian carcinoma [63]. (5) Complement C4 (CO4) was reported as a lung cancer biomarker for diagnosis and prognosis [30,64]. (6) Upregulation of Syndecan-4 (SDC4) was reported to contribute to the TGF-β1-induced epithelial to mesenchymal transition in lung adenocarcinoma A549 cells [65].…”
Section: Parallel Reaction Monitoring (Prm) Validationmentioning
confidence: 99%
“…C4d, a complement split product derived from the classical pathway activation, is deposited in a wide range of primary tumors, including lung cancer, papillary thyroid carcinoma, astrocytoma, and follicular and MALT lymphoma . Soluble C4d was increased in biological fluids from lung and oropharyngeal cancer patients and may be of value for diagnosis and prognosis . Abnormalities in the activation of the classical pathway have been described in patients with chronic lymphatic leukemia .…”
Section: Complement Activation In Cancermentioning
confidence: 99%
“…33,[35][36][37] Soluble C4d was increased in biological fluids from lung and oropharyngeal cancer patients and may be of value for diagnosis and prognosis. 33,38,39 Abnormalities in the activation of the classical pathway have been described in patients with chronic lymphatic leukemia. 40,41 Finally, complement components, compatible with classical pathway activation, were abundantly present in endometriosis and ovarian cancer, whereas normal endometrium showed little to no expression of these factors.…”
Section: Complement and Cancer Immunosurveillancementioning
confidence: 99%